Queen control - Bong, Joseph Choon Fah; King, Patricia Jie Hung (Universiti Putra Malaysia Press, 2013)
In a termite colony, the queen termite is the central figure which performs the vital task of procreation by laying thousands of eggs per day to give rise to the enormous number of termites within the colony. She does not work and rarely moves, but grows to very large size in the queen's chamber.